2014
DOI: 10.1891/0730-0832.33.2.66
|View full text |Cite
|
Sign up to set email alerts
|

NICU Parent-to-Parent Partnerships: A Comprehensive Approach

Abstract: Parents of newborns in the neonatal intensive care unit (NICU) find themselves in a world of unknown medical terminology, advanced technology, and the realization that their dream of a healthy baby has been shattered. The unique partnership with trained parent-to-parent volunteers, who have had previous NICU experiences, enhances professional support and helps new NICU parents adjust to these unexpected challenges. This practice-based article describes the Helen DeVos Children's Hospital NICU Parent-to-Parent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…These results show the great sensibility of Italian NICU staff regarding the involvement of families in the care of their infants but also the lack of consciousness of considering families (single family, family associations and volunteering) as a real resource for the NICU organisational not exclusively for their own baby. Several studies have demonstrated the benefits of partnership and the active role family members in championing the organisation in various healthcare settings (Bookout et al, 2016;Cunningham and Walton, 2016;Halm et al, 2006;Landis, 2007;Levick et al, 2014;Wadsworth and Harmer, 2016;Zarubi et al, 2008). Therefore, we believe that more efforts should be made to raise awareness among NICU staff about the importance of partnering with families but also to develop policies and procedures supporting the participation of parents as part of an interdisciplinary team (Craig et al, 2015;Marini et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…These results show the great sensibility of Italian NICU staff regarding the involvement of families in the care of their infants but also the lack of consciousness of considering families (single family, family associations and volunteering) as a real resource for the NICU organisational not exclusively for their own baby. Several studies have demonstrated the benefits of partnership and the active role family members in championing the organisation in various healthcare settings (Bookout et al, 2016;Cunningham and Walton, 2016;Halm et al, 2006;Landis, 2007;Levick et al, 2014;Wadsworth and Harmer, 2016;Zarubi et al, 2008). Therefore, we believe that more efforts should be made to raise awareness among NICU staff about the importance of partnering with families but also to develop policies and procedures supporting the participation of parents as part of an interdisciplinary team (Craig et al, 2015;Marini et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Such findings are similar to those described by other researchers, who report the difficulties mothers undergo to establish a bond with their children when they do not have a close contact with them right after their birth; 1,4,7 , the feeling of impotence toward caring for the child at home after the infant is discharged from the hospital; [5][6]8,10 the doubts and uncertainties as to how to perform some care activities and how to modify them as the baby grows and changes, as well as the feeling of not being a real mother but a fearful person that is incapable of taking care of her child without the support of healthcare professionals. [4][5][6][14][15][16] Throughout the pre and postnatal period, the professional nurse is recognized as the one being in more contact with the woman. For this reason, nursing should lead the actions aimed at supporting the women going thru the second and third phases of the process of becoming a mother.…”
Section: Discussionmentioning
confidence: 99%
“…Parent‐to‐parent mentoring and support can take many different forms, such as one‐to‐one partnering, parent support groups, visiting parents, or veteran parents. Training programmes for parents have been put in place and the overall experience has been positive . Another strategy involves a part‐time parent‐to‐parent manager (hired because of prior experience of having an infant in the NICU).…”
Section: The ‘Our‐hope’ Approachmentioning
confidence: 99%
“…Training programmes for parents have been put in place and the overall experience has been positive. 92 Another strategy involves a part-time parent-to-parent manager (hired because of prior experience of having an infant in the NICU). This approach has been reported as useful to implement familycentred care and formalize a series of services for parents.…”
Section: Relevancementioning
confidence: 99%